MENINGKATKAN KEMAMPUAN KELINCAHAN PEMAIN UKM SEPAKBOLA UNIVERSITAS WAHID HASYIM MELALUI LATIHAN LADDER DRILL TAHUN 2017 - Yudhi Purnama; Muhlisin Muhlisin (LP2M, 2018)
Proper practice method is an important element in improving the ability of agility, amongothers, using ladder drill tool or stair ladder. Rapid foot reaction becomes one form ofphysical exercise that works to train foot agility and coordination in a balanced manner. Thepurpose of this research is to know how big influence of ledder drill training to the agility offootball player player from Unwahas. This study uses the design of One Group Pretest-Posttest Design research, with a population of players Football Unwahas SMEs, as many as40 players. The sample used in this research is 28 people, data analysis of research done bycomparing data of pretest and posttest result after treatment using one sample t-test. Theresults obtained that the average agility time of pretest result is 16.73 seconds, with thehighest time of 21.6 seconds and the lowest time 14.6 seconds. While at the post test, theaverage agility time is 15.76 seconds, the highest time is 19.2 seconds and the lowest time is14.2 seconds. Ho is rejected and Ha is accepted because sig = 0,000 <0,05, it meansdifference of difference is different so it can be said effective ladder drill treatment toincrease the result of agility. The result of research is sig = 0.000 <0,05, it means differenceof difference is different so it can be said effective ladder drill treatment to increase the resultof agility, so it can be concluded that there is influence between ladder drill training to abilityagility.Keywords: influence, ladder drill, agility, ukm football